Economic Transformation through Digitalization: Case Study of SMEs and E-Commerce Platforms - Albertus Maria Setyastanto; Syaiful , Syaiful (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines the economic transformation process occurring within Micro, Small, and Medium Enterprises (MSMEs) through integration with e-commerce platforms in Indonesia. Using a case study method involving 5 MSMEs in East Java, this research analyzes changes in business models, revenue growth, market expansion, and operational adaptations experienced by MSME actors after joining e-commerce platforms. The findings indicate that digitalization through e-commerce platforms provides an average revenue increase of 45%, expansion of market reach to international markets, and business operational efficiency. However, several obstacles such as digital literacy gaps, uneven infrastructure, and intensifying competition were also identified. This research contributes to understanding the dynamics of digital transformation in MSMEs and provides strategic recommendations for business actors and policymakers to optimize the utilization of e-commerce platforms in local economic development.